Wilkie Collins, Vera Caspary and the evolution of the casebook novel - Emrys, A. B., 1946- (McFarland & Company, Inc., Publishers, 2011)
"Wilkie Collins was one of the most popular novelists during England's Victorian era. This critical study explores his formal ingenuity, particularly the novel of testimony constructed from epistolary fiction, trial reports, and prose monologue. This text explores how the formal dialogue between Collins and Vera Caspary has linked sensation fiction with noir thrillers and film noir"--Provided by publisher.